Teacher Pay and Student Performance: Evidence from the Gambian Hardship Allowance - Todd Pugatch; Elizabeth Schroeder (Institute for the Study of Labor (IZA), 2014)
We evaluate the impact of the Gambian hardship allowance, which provides a salary premium of 30-40% to primary school teachers in remote locations, on student performance. A geographic discontinuity in the policy's implementation provides identifying variation. We find no effects of the hardship allowance on average student performance. These null average effects hide important heterogeneity, with learning gains for students at the top of the distribution and losses for those at the bottom. With over two dozen developing countries implementing similar policies to increase teacher compensation in rural schools, this study offers important evidence on their effectiveness.
Keywords: I25; I28; J38; J45; O12; O15; 330; teacher compensation; rural schools; Gambia; program evaluation; regression discontinuity